MENILAI EFEK MODERASI DARI TATA KELOLA PERUSAHAAN PADA HUBUNGAN INTELLECTUAL CAPITAL DAN KINERJA PASAR - Prasojo Prasojo; Muhammad Yusuf Shalihin (Jurnal Magister Akuntansi Trisakti, 2022)
This study relates the relationship between Intellectual Capital (IC) and the company's market performance as moderated by corporate governance. The results of this study prove that the total value-added intellectual capital (VAIC) does not have a significant effect on the company's market performance. Partially only CEE has a significant positive effect on the company's market performance. HCE has a negative and significant relationship, meanwhile, SCE has a positive but insignificant correlation to the company's market performance. The samples used in this study were all companies included in the LQ45 index category in the 2015-2018 period. Statistical data processing is carried out through panel data testing with the fixed-effect method. The research contributes to potential investors in making investment decisions by considering the existence of IC and corporate governance as part of the investor analysis. The results of this study are also expected to provide empirical evidence about the relationship between IC, CG, and market performance in Indonesia. These findings will expand the IC literature in business operations in Indonesia concerning the role of IC on its direct impact on market performance. Contribution to regulators, disclosure, and presentation of IC is related to PSAK 19 which has been adopted from IAS 38.